Chemoinformatic design and profiling of some derivatives of 1, 2, 4-oxadiazole as potential dengue virus NS-5 inhibitors - Samuel Ndaghiya Adawara; Gideon Adamu Shallangwa; Paul Andrew Mamza; Ibrahim Abdulkadir (Bulletin of the National Research Centre, 2022)
Abstract Background Dengue virus (DENV) infection is spreading rapidly, especially in the subtropical and tropical regions, placing a huge percentage of the global population at risk and causing repeated outbreaks. DENV protease inhibition has been suggested as a viable therapeutic strategy. Using a computer-aided design approach and the structure-based drug design approach, ten 1, 2, 4-oxadiazole derivatives were designed based on the lead template (34) from our prior study. The design involved the substitution at the phenyl pharmacophore of the lead with methylamine, hydroxyl, and methoxy groups. To compare the anti-DENV efficacy of the optimized designed compounds to the template and other DENV referenced inhibitors targeting the NS-5 protease (PDB ID: 5K5M), they were docked with the DENV NS-5 protease. In silico, ADME characteristics and drug-likeness were also assessed for the compounds. Results The molecular docking scores of the designed 1, 2, 4-oxadiazole derivatives varied from − 19.091 to − 29.61 kcal/mol, with excellent hydrogen bond energies in the range of − 3.402 to − 9.0128 kcal/mol, compared to the lead with a score of − 19.10 kcal/mol, and the hydrogen bond energy is − 3.10 kcal/mol, both of which are lower than those of the proposed compounds. Ferentinide, S-adenosyl-l-homocysteine, and Ribavirin were found to have lower binding scores of − 15.8137, − 16.5362, and − 12.446 kcal/mol, respectively, with hydrogen bond energies of − 4.2659, − 10.4372, and − 7.2995 kcal/mol. The developed compounds all followed Lipinski's criteria, meaning they were highly bioavailable, had no potential carcinogenic or mutagenic properties, and posed no concern of cardiovascular toxicity based on the ADMET profile. Conclusion The proposed oxadiazole derivative interacted better with DENV protease (NS-5) than the lead inhibitor as well as the conventional inhibitors. Compounds 34a and 34b had the best ligand-protease interaction and gave the lowest free energy at − 26.54 and − 29.612 kcal/mol, respectively. Hence, they could be suggested as potential therapeutic candidates to inhibit NS-5 RdRp protease. This study has revealed the anti-DENV action of the designed compounds, indicating that synthesis and in vivo studies into their efficacy and mechanism are warranted.